A Proposal for the Pollution Management Reform in Lithuania: “Pollution currency” Approach (part 1) - Čekanavičius, Linas (Ekonomika, 1998)
The idea of a universal “pollution currency” that should be used for “payments” for the right to emit specified types of pollutants into air or water is introduced. It is argued that the universal and transferable emission coupons (UTEC) concept actually integrates the main advantages of emission taxes and marketable pollution permits systems, while avoiding some of their less desired qualities. “Numerous opportunities exist to improve environmental protection and natural resource management with incentive-based policy reforms, but they must be assessed on a case-bycase basis” (Project 88/Round II, U.S. Congress).